Molecular diversity of Mycobacterium tuberculosis strains indifferent provinces of Iran - Mozafari, Mohadese (Iran J Microbiol, 2013)
BACKGROUND AND OBJECTIVES: Molecular epidemiology tools are widely used in determining epidemiology of tuberculosis. Spoligotyping is a molecular epidemiology method that is used for characterization and typing of Mycobacterium tuberculosis complex strains. The method is based on polymorphism of the chromosomal DR locus consisting of identical 36-bp DRs alternating with 35-41 unique spacers. The objective of this study was to investigate the prevalence of M. tuberculosis spoligotypes in different provinces of Iran. MATERIALS AND METHODS: M. tuberculosis strains were isolated from TB patients of Mycobacteriology Research center (MRC). DNA was extracted from patient’s clinical samples. PCR was performed by using of specific primers for DR region. The amplified DNA was hybridized to the spoligotyping Membrane. Hybridized DNA was detected with ECL detection kit and by exposing ECL Hyperfilm to the membrane. The obtained result was entered to a binary format and was analyzed using SpolDB4 database. RESULTS: Spoligotyping resulted in 136 different patterns. Out of 1242 M. tuberculosis strains, 1165 strains (93.8%) were classified into 59 clusters and the remaining strains (6.2 %) were singleton. CONCLUSIONS: The results of present study showed that strains of CAS family were more prevalent than other strains in Iran. Other prevalent families were Haarlem, T and Beijing, respectively.